A dozen lessons for entrepreneurs - Griffin, Trenholme J. (Columbia University Press, 2017)
A Dozen Lessons for Entrepreneurs shows how the insights of leading venture capitalists can teach readers to create a unique approach to building a successful business. Griffin argues that innovation and best practices are discovered by the experimentation of entrepreneurs as they establish the evolutionary fitness of their business. The products and services created through this experimentation that have greater fitness survive, and less-fit products and services die.